Recall that the slope-intercept form of the equation of a line is:
![y=mx+b,](https://img.qammunity.org/2023/formulas/mathematics/college/4dutw7uwqnrl059bgov2p1mbj6cypja7zr.png)
where m is the slope of the line and b is the y-intercept.
To take the given equation to its slope-intercept form, first, we multiply it by x+1 and get:
![\begin{gathered} y+13=6(x+1), \\ y+13=6x+6. \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/e7mifubbx0qe4hterkt3vn6fzy3x19c1ko.png)
Subtracting 13, we get:
![\begin{gathered} y=6x+6-13, \\ y=6x-7. \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/awmksnddxsalwz0ruvpwuf6cg2gebzkqqx.png)
Answer:
![y=6x-7.](https://img.qammunity.org/2023/formulas/mathematics/college/oxclgy0qzk8g2fkw6wg3us9kf2u9gp016d.png)